2007
DOI: 10.1039/b709982g
|View full text |Cite
|
Sign up to set email alerts
|

Single laser pulse induced aggregation of gold nanoparticles

Abstract: Gold nanoparticles with an average diameter of 11 nm (Au(39000)) were prepared in an SDS aqueous solution. A 80-microm liquid droplet (microdroplet) of the solution was ejected into the atmosphere from a microdroplet nozzle. Structural changes of the gold nanoparticles in the microdroplet, after they were irradiated with a focused single-nanosecond laser pulse at the wavelength of 532 nm, were studied by transmission electron microscopy (TEM) and optical absorption spectroscopy. It was revealed that the gold n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…[101][102][103] In presence of stabilizers, the average size of particles after fragmentation is reduced than in pure water, which confirmed that fragments are inclined to regrow. [101][102][103] According to these results, the minimum diameter is determined by the equilibrium between the efficiency of fragmentation and reaggregation. [101][102][103] For low aggregation efficiency, the minimum diameter can be reached by sequential irradiation with more than one laser pulse.…”
Section: Size Manipulation By Laser Irradiationsupporting
confidence: 76%
See 3 more Smart Citations
“…[101][102][103] In presence of stabilizers, the average size of particles after fragmentation is reduced than in pure water, which confirmed that fragments are inclined to regrow. [101][102][103] According to these results, the minimum diameter is determined by the equilibrium between the efficiency of fragmentation and reaggregation. [101][102][103] For low aggregation efficiency, the minimum diameter can be reached by sequential irradiation with more than one laser pulse.…”
Section: Size Manipulation By Laser Irradiationsupporting
confidence: 76%
“…Mafune´and co. investigated also the fate of AuNP fragments in presence or absence of stabilizers. 62,87,[101][102][103] They found that fragments can coalesce forming spherical particles or, when present with high concentration, elongated fractal structures. [101][102][103] In presence of stabilizers, the average size of particles after fragmentation is reduced than in pure water, which confirmed that fragments are inclined to regrow.…”
Section: Size Manipulation By Laser Irradiationmentioning
confidence: 99%
See 2 more Smart Citations
“…[64][65][66][67][68] It has been reported also that Au atoms and small clusters form during photofragmentation of Au nanoparticles in liquid phase. 54,69 Photofragmentation of Au nanospheres contributes to F ab also by increasing the concentration of Au particles and solution temperature. 54,69 Photofragmentation of Au nanospheres contributes to F ab also by increasing the concentration of Au particles and solution temperature.…”
Section: Introductionmentioning
confidence: 99%